Proteomics and Phosphoproteomics of Heat Stress-Responsive Mechanisms in Spinach - Zhao, Qi; Chen, Wenxin; Bian, Jiayi; Xie, Hao; Li, Ying; Xu, Chenxi; Ma, Jun; Guo, Siyi; Chen, Jiaying; Cai, Xiaofeng; Wang, Xiaoli; Wang, Quanhua; et al. (Frontiers in Plant Science, 2018)
Elevated temperatures limit plant growth and reproduction and pose a growing threat to agriculture. Plant heat stress response is highly conserved and fine-tuned in multiple pathways. Spinach (Spinacia oleracea L.) is a cold tolerant but heat sensitive green leafy vegetable. In this study, heat adaptation mechanisms in a spinach sibling inbred heat-tolerant line Sp75 were investigated using physiological, proteomic, and phosphoproteomic approaches. The abundance patterns of 911 heat stress-responsive proteins, and phosphorylation level changes of 45 phosphoproteins indicated heat-induced calcium-mediated signaling, ROS homeostasis, endomembrane trafficking, and cross-membrane transport pathways, as well as more than 15 transcription regulation factors. Although photosynthesis was inhibited, diverse primary and secondary metabolic pathways were employed for defense against heat stress, such as glycolysis, pentose phosphate pathway, amino acid metabolism, fatty acid metabolism, nucleotide metabolism, vitamin metabolism, and isoprenoid biosynthesis. These data constitute a heat stress-responsive metabolic atlas in spinach, which will springboard further investigations into the sophisticated molecular mechanisms of plant heat adaptation and inform spinach molecular breeding initiatives.